Pembuatan Batik Jumputan di RT 10 RW 02 Tanjung Barat Jagakarsa Jakarta Selatan (Neolectura, 2023)
One of the obligations of lecturers within the framework of the Tri Darma of Higher Education is community service, apart from education/teaching and research. The team of lecturers from the Visual Communication Design Study Program (DKV) is expected to use DKV knowledge as a basis for an approach to solving problems faced by the community to become a field of work in community service. The abdimas partners are PKK women cadres who are also housewives in the Tanjung Barat sub-district, Jagakarsa sub-district, South Jakarta. Their number is about 15 people who are already forty years old on average but still want to increase their family income by producing and selling merchandise but they don't have production skills. This desire is motivated by Indonesia's declining economic condition so that it is not sufficient for their daily needs. This community service solution can be seen as a contribution to efforts to preserve batik, especially jumputan as part of the Indonesian nation's cultural identity which has been in decline since the mid-20th century. Now most of the batik circulating in the market is printed batik which is actually not batik and some are imported products